The discoloration effect of diluted minocycline containing triple antibiotic gel used in revascularization - Alaa H.A. Sabrah; Ayah A. Al-Asmar; Firas Alsoleihat; Heba Al-Zer (Elsevier, 2020)
Background/purpose: Triple antibiotic paste (TAP) has been successfully used in revascularization procedure. However, one of the problems associated with TAP use is teeth discoloration, which is attributed to the presence of minocycline constituent. The aim of this study is to investigate the discoloration effect of different concentrations of triple (TAP) and double (DAP) antibiotics pastes on root dentine. Materials and methods: Sterilized dentine specimens (4 × 4 × 1) were prepared, and randomly assigned to 5 groups; 1000 mg/mL of Triple antibiotic paste (TAP), 1000 mg/mL of Double antibiotic paste (DAP), 1 mg/mL of TAP in Methylcellulose gel (MTAP), 1 mg/mL of DAP in Methylcellulose gel (MDAP), and distilled water control groups (n = 12). The assigned treatment was applied for 14 days. The CIE L*a*b calorimetric parameters were measured for all dentine specimens using a Chroma meter. One-way ANOVA and multiple comparisons were used for statistical analyses (p < 0.05). ΔE for the different treatments as compared to distilled water group was calculated. Results: TAP and MTAP groups significantly affects the L* values of the root dentine (p < 0.05). ΔE change was noticeable between TAP and MTAP compared to the distilled water group. Conclusion: The incorporation of minocycline in TAP medicaments, even in low concentrations, can still provoke a noticeable tooth discoloration.